Campaign Warriors : Political Consultants in Elections - Nelson, Candice J., 1949-; Thurber, James A., 1943- (Book collections on Project MUSE., 2000)
"The essays in this volume present original data and analysis describing the world of campaign consultants. The nine chapters examine and analyze: the diversity and complexity of the consulting business and consultants' attitudes about candidates, voters, political parties, the media, ethics, and the need for reform; the impact of consultants on fundraising, strategy, and communications, and the electoral success of consultants in congressional elections, initiatives, and referenda; and the internationalization of election campaign consultancy and the spread of political consultancy worldwide." "Campaign Warriors illuminates the work of professional political consultants and their growing influence on the electoral process and American democracy."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.